TRENDS AND ISSUES IN RELATION TO ALCOHOL DEPENDENCE IN THE ARMED FORCES - RAJU, MSVK (Med J Armed Forces India, 2002)
Alcohol dependence syndrome has an estimated prevalence of 1533% of all psychiatric hospitalizations in a year. There is an increasing trend in incidence among JCOs/ORs. The index of admission was highest in Armoured Corps, Mechanized Infantry and Army Medical Corps (AMC). Generally a service personnel becomes dependent at 35 years of age after about 11 years of drinking. The average consumption of alcohol dependent individuals was 6-7 pegs/day. A family history of alcohol abuse/dependence was found in 31 % cases. Alcoholics had high anxiety, depression, extroversion, neuroticism and psychopathic deviate traits. Alcoholism was associated with significantly low self esteem. Significantly more alcoholics were alexithymic as compared to non-alcoholics. The γ glutamyl transferase (GGT) and mean corpuscular volume (MCV) were found to be useful diagnostic aids for alcoholism. Almost a third of alcoholics have potentially serious physical problems, 20% suffer from various degrees of psychotic phenomena, 40-55% have significant marital, occupational and disciplinary problems, while 3-6.93% attempted deliberate self-harm. Despite wide variations in mode of disposal, after diagnosis only a small percentage of alcoholics remain in service beyond three years. There is need for concerted investigations into the precipitating and perpetuating factors, co-morbidity, the process of change towards betterment and the long-term outcome of alcoholism in service personnel.